Barbados. Significant Achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Barbados during 2019 are identified, with respect to the needs and interests of the country, strengthening the collaboration of the public and private sectors, as well as the link between the agri-food sector and tourism, through workshops for the implementation of policies on agrotourism. Likewise, work was done on issues such as apiculture, climate change, gender equality in the agricultural sector and in livestock and livestock reproduction. Finally, work was done on financing and support for small producers.